A new life model of tripod type Constant Velocity Joint using accelerated life test. (April 2019) - Kim, Dong Wan; Kim, Seong Han; Chu, Chong Nam; Cho, Jeong Hyeon
Abstract: This study proposes a new wear life model, focusing on the adhesive wear phenomena that occur in tripod type CVJs. For the development of the wear life model, kinematic analysis was performed to derive the relative coordinates of components and contact points. Then, the normal pressure at the contact points were calculated. In order to investigate the wear amount of each contact point, an Accelerated Life Testing (ALT) based on a reliability analysis theory was employed. In this study, a new experimental system was built to experiment the wear of CVJ components, which enables to measure the wear amount under much harsher conditions than actual driving conditions. The experimental results from the ALT were analyzed and organized for the wear life model. Finally, the developed model was verified by comparing the estimated results with the experimental results under an actual driving condition. Highlights: A new wear life model for tripod type CVJs is developed based on theoretical analysis and accelerated life test results. The developed wear experiment system measures the exact wear amount of tripod type CVJs. The wear life predicted by the model, which was proven experimentally, is very accurate.